2016
DOI: 10.1590/1414-49802016.00100010
|View full text |Cite
|
Sign up to set email alerts
|

Padres adolescentes y jóvenes: debates y tensiones

Abstract: Resumen Este artículo delinea un panorama general de la literatura, nacional e internacional, consultada en la primera fase de la investigación Visibilizando la Paternidad Adolescente, desarrollada en el Departamento de Trabajo Social de la Universidad de la República, Uruguay. Pretende indagar las experiencias de paternidad de adolescentes y jóvenes pobres en el Uruguay actual. Identifica algunos puntos neurálgicos presentes en el debate actual sobre el tema

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
(2 reference statements)
0
5
0
4
Order By: Relevance
“…Evidence has shown that early fatherhood and motherhood are not independent of the sociocultural and economic contexts of societies and the population subgroups that comprise them [6][7][8][9][10][11]. Becoming a parent is mediated by the experiences that each person has, where constructing the meaning of motherhood and fatherhood is determined by patterns of the ideological, cultural, and religious order of the social context, which impact their interactions in daily life and its discourse [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that early fatherhood and motherhood are not independent of the sociocultural and economic contexts of societies and the population subgroups that comprise them [6][7][8][9][10][11]. Becoming a parent is mediated by the experiences that each person has, where constructing the meaning of motherhood and fatherhood is determined by patterns of the ideological, cultural, and religious order of the social context, which impact their interactions in daily life and its discourse [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…2,5 Becoming a mother, father, or child is a series of events in which a set of elements related to cultural and ideological decisions and practices of interaction that make up daily life are added, fusing to emerge with the meanings that men and women give to a child. 5,6 In Colombia, one in ve women under the age of 19 have been pregnant; therefore, it is considered as a country with high rates of adolescent pregnancy. 7 According to the National Administrative Statistics Department, in 2019, 4,713 children were born to mothers aged between 10 and 14 years, and 116,609 were born to mothers aged between 15 and 19 years.…”
Section: Introductionmentioning
confidence: 99%
“…Desde algunas perspectivas, se estima a los padres y madres en condición juvenil como personas no aptas para llevar a cabo la crianza de niños y niñas, y como una época, refiriéndose a la edad, en la que estos jóvenes deberían realizar proyectos de otro ámbito (Bermudez, 2016;Rengifo & Palacio, 2016). No obstante, a pesar del estigma que se cierne sobre este grupo de sujetos en este aspecto, estos se unen, tienen hijos y construyen, en términos de Goffman (2001) una carrera práctica en la crianza de acuerdo con su contexto y ámbito cultural (Aguirre, 2015); en ese sentido afrontan de manera diversa maternidades y paternidades (Lugo, 2016;Hasicic, 2018;Henao & Villa, 2018;Huerta, 2018;De Arújo, Da Silva, Da Silva, Camurça, & Reis, 2016).…”
Section: Introductionunclassified